Active disturbance rejection control for nonlinear systems : an introduction - Guo, Bao-Zhu; Zhao, Zhi-Liang (John Wiley & Sons, 2016)
A concise, in-depth introduction to active disturbance rejection control theory for nonlinear systems, with numerical simulations and clearly worked out equations * Provides the fundamental, theoretical foundation for applications of active disturbance rejection control * Features numerical simulations and clearly worked out equations * Highlights the advantages of active disturbance rejection control, including small overshooting, fast convergence, and energy savings